Stimulated saprotrophic fungi in arable soil extend their activity to the rhizosphere and root microbiomes of crop seedlings. (15th June 2021) - Clocchiatti, Anna; Hannula, S. Emilia; Hundscheid, Maria P. J.; klein Gunnewiek, Paulien J. A.; de Boer, Wietse
Summary: Saprotrophic fungi play an important role in ecosystem functioning and plant performance, but their abundance in intensively managed arable soils is low. Saprotrophic fungal biomass in arable soils can be enhanced with amendments of cellulose‐rich materials. Here, we examined if sawdust‐stimulated saprotrophic fungi extend their activity to the rhizosphere of crop seedlings and influence the composition and activity of other rhizosphere and root inhabitants. After growing carrot seedlings in sawdust‐amended arable soil, we determined fungal and bacterial biomass and community structure in roots, rhizosphere and soil. Utilization of root exudates was assessed by stable isotope probing (SIP) following 13 CO2 ‐pulse‐labelling of seedlings. This was combined with analysis of lipid fatty acids (PLFA/NLFA‐SIP) and nucleic acids (DNA‐SIP). Sawdust‐stimulated Sordariomycetes colonized the seedling's rhizosphere and roots and actively consumed root exudates. This did not reduce the abundance and activity of bacteria, yet higher proportions of α‐Proteobacteria and Bacteroidia were seen. Biomass and activity of mycorrhizal fungi increased with sawdust amendments, whereas exudate consumption and root colonization by functional groups containing plant pathogens did not change. Sawdust amendment of arable soil enhanced abundance and exudate‐consuming activity of saprotrophic fungi in the rhizosphere of crop seedlings and promoted potential beneficial microbial groups in root‐associated microbiomes.